2022
DOI: 10.3389/fcell.2022.840171
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis Reveals the Gut Microbial Metabolite TMAO Promotes Inflammatory Hepatocellular Carcinoma by Upregulating POSTN

Abstract: Liver cancer has a high mortality rate. Chronic inflammation is one of the leading causes of hepatocellular carcinoma. Recent studies suggested high levels of trimethylamine N-oxide (TMAO) may correlate with increased risk of inflammatory-induced liver cancer. However, the mechanisms by which TMAO promotes liver cancer remain elusive. Here, we established a model of inflammatory-induced liver cancer by treating Hepa1-6 cells and Huh7 cells with TNF-α. TMAO synergistically increased the proliferation, migration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Previous studies have reported a positive correlation between the upregulation of POSTN and poor overall survival in human hepatocellular carcinoma (HCC) 14 . Additionally, high expression levels of POSTN have been found to positively correlate with neutrophil in ltration, thereby promoting tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported a positive correlation between the upregulation of POSTN and poor overall survival in human hepatocellular carcinoma (HCC) 14 . Additionally, high expression levels of POSTN have been found to positively correlate with neutrophil in ltration, thereby promoting tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Dysbiosis of gut microbiota and increased intestinal permeability result in NAFLD progression by increasing the transportation of gut-microbiotaderived components and metabolites into the liver [62]. For example, gut-microbiota-derived metabolite trimethylamine N-oxide (TMAO) from dietary choline, carnitine, and L-carnitine can aggravate hepatic steatosis in NAFLD by regulating BA metabolism through the regulation of farnesoid X receptor (FXR) signaling pathway [63]. In vitro treatment of TMAO together with pro-inflammatory cytokine TNF-α can increase the proliferation (detected by the cell-counting Kit-8 assay), migration (detected by the wound healing assay and the transwell assay), and invasion [detected by the expression levels of periostin, integrin-linked kinase (ILK)/RAC-α serine/threonine-protein kinase (AKT1), and the mammalian target of rapamycin (mTOR)] of mouse liver cancer cell line Hepa1-6 cells and human liver cancer cell line Huh7 cells [64].…”
Section: Dysbiosis Of Gut Microbiotamentioning
confidence: 99%
“…However, it inhibits the production of endothelial nitric oxide (NO) synthase and NO[ 41 ]. It has also been reported that TMAO can promote inflammatory hepatocellular carcinoma by inducing ROS and activating ILK/AKT/mammalian target of rapamycin (mTOR) signaling via POSTN[ 42 ]. Our previous studies showed that administration of TMAO produced a novel model of frailty in mice[ 43 ].…”
Section: The Underlying Mechanism Of the Influence Of The Gm On Frail...mentioning
confidence: 99%